2016
DOI: 10.1177/1352458516661640
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of spasticity following intermittent theta burst stimulation in multiple sclerosis is associated with modulation of resting-state functional connectivity of the primary motor cortices

Abstract: This longitudinal resting-state fMRI study evidences that functional reorganization of the primary motor cortices may underlie the effect of iTBS on spasticity in MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
66
0
16

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(83 citation statements)
references
References 29 publications
1
66
0
16
Order By: Relevance
“…Boutière et al . showed that 10 sessions of iTBS resulted in a statistically significant change in interhemispheric connectivity with a correlation with the severity of the antispastic effect .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Boutière et al . showed that 10 sessions of iTBS resulted in a statistically significant change in interhemispheric connectivity with a correlation with the severity of the antispastic effect .…”
Section: Discussionmentioning
confidence: 98%
“…It has been shown that HF-rTMS leads to inhibition of the Hreflex, which may be due to an increase in presynaptic inhibition of Ia afferents [6]. Bouti ere et al [16] showed that 10 sessions of iTBS resulted in a statistically significant change in interhemispheric connectivity with a correlation with the severity of the antispastic effect [13].…”
Section: Discussionmentioning
confidence: 99%
“…The postulated pathophysiology of spasticity is that lesions of upper motor neuron impair the supraspinal inhibitory inputs, leading to an increased excitability of α and γ motor neurons, and of the interneurons at the spinal level, ultimately causing spasticity [34,35]. Therefore, facilitatory rTMS and iTBS had been applied to lower spasticity in patients with a number of neurologic disorders [20,33,[36][37][38][39][40][41] by modulating the excitability of cortical motor neurons. In addition, it is increasingly accepted that iTBS may modulate cortical excitability by inducing the long-term potential-like (LTP-like) plasticity changes [10,42,43], and the persistently increasing neural activity may project to inhibitory corticospinal synapses.…”
Section: Discussionmentioning
confidence: 99%
“…PubMed search identified 12 references regarding repetitive magnetic stimulation. In total, five studies [51][52][53][54][55] fulfilled the inclusion criteria for this review. Four major outcomes were used in the studies: the MAS [51][52][53][54], the AS [55], the MSSS-88 [54] and the spasticity VAS [51].…”
Section: Repetitive Transcranial Magnetic Stimulation (Rtms)mentioning
confidence: 99%
“…In total, five studies [51][52][53][54][55] fulfilled the inclusion criteria for this review. Four major outcomes were used in the studies: the MAS [51][52][53][54], the AS [55], the MSSS-88 [54] and the spasticity VAS [51]. Three study designs were double-blind sham-controlled, randomized controlled trials [51,54,55] and two were pseudo-randomized sham-controlled studies [52,53].…”
Section: Repetitive Transcranial Magnetic Stimulation (Rtms)mentioning
confidence: 99%